The effect of mobile-assisted Cerf English vocabulary profile word lists on L2 students’ vocabulary knowledge / Zailin Shah Yusoff ... [et al.] - Yusoff, Zailin Shah; A. A. Gurmani, Muhammad Taimoor; Sanif, Sazuliana; Mohd Noor, Siti Noor Fazelah (Universiti Teknologi MARA, 2022)
The objective of the study was to examine the effect of mobile-assisted vocabulary learning using the Common European Framework of Reference for Languages (CEFR) English Vocabulary Profile word lists on L2 students’ vocabulary knowledge at a university in Pakistan. A quasiexperimental study was conducted with sixty samples divided into the experimental (n=30) and control (n=30) groups. The treatment for the experimental group comprised ten weeks of mobile-assisted vocabulary input from the chosen word lists. The Vocabulary Size Test (Nation & Beglar, 2007) was administered as pre-test and post-test to measure the impact of the word lists. Results from the independent t-test showed a significant effect of the treatment on the experimental group, and improvement was observed in the mean score. When the post-test mean scores of the control and experimental groups were compared, findings indicated that there was a difference in the mean scores and the mean difference between groups was significant. The primary conclusion of this study is that the mobile-assisted vocabulary input did significantly help improve the experimental group’s mean score, illustrating its impact on the group’s vocabulary knowledge. This, essentially, points to the fact that this method for vocabulary learning can be recommended for L2 learners and may be used to improve their vocabulary in line with the CEFR levels.